The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878 - Pachelle, Paulo P.g.; Tavares, Marcos (Zootaxa, 2018)
The present revision is based on the largest sample of Euryrhynchidae Holthuis, 1950 studied to date, with special reference to Euryrhynchus Miers, 1878. The revision confirms the validity of the 8 currently recognized species of Euryrhynchidae and describes 2 new species related to Euryrhynchus amazoniensis Tiefenbacher, 1978: E. taruman sp. nov. and E. tuyuka sp. nov. The species Euryrhynchus amazoniensis, E. burchelli Calman, 1907, E. pemoni Pereira, 1985 and E. wrzesniowskii Miers, 1878 are redescribed and illustrated based on specimens from the type series and additional material. Additional diagnostic characters are proposed to differentiate the species of Euryrhynchus, previously separated only by the armature of the second pereopod carpus and merus.